Depressão pós-parto: um olhar psicanalítico - Julien, Maria Claudia Gomes (2013)
This paper is aimed at studying postpartum depression through the analysis of a clinical case and a testimony-book from women that had suffered this type of depression. It is related to primiparous mothers that idealized motherhood and presented a huge suffering in taking care of the newborn. The intent was to to investigate the woman condition in regards to motherhood, family and breastfeeding through history in order to position the contemporary woman. Through Freud and Klein psychoanalytic studies, it was investigated how female psychism and how the desire for being a mother arises. Postpartum depression was analyzed in light of psychoanalytic theory references. The findings on this paper suggest that postpartum depression has multiple origins, including a demanding superego, connection (or absence of) to maternal figure and idealizations as a result of cultural influences, however the personal history of the woman plays an important role. Through the mankind history the importance of the women was built, going from Eve (the sinner) to an image of Holly Virgin. This idealized view of women heavily disturbs the exercise of motherhood. According to the abovementioned authors, during postpartum a woman is exposed to her origins, her beginnings and meets her primitive history, unconscious and marked by ambiguity of intense feelings. On the clinical cases analyzed by the author of this paper as well as on the narrative from the testimony-book all the above variables seem to be present as precedent conditions to postpartum depression